1989
DOI: 10.1177/00957984890152008
|View full text |Cite
|
Sign up to set email alerts
|

African-Centered Theses on Mental Health and a Nosology of Black/African Personality Disorder

Abstract: Mental health is defined and a diagnostic system of ordered and disordered African (Black) personality functioning is discussed. The discussion first is grounded in the backdrop of briefly stated but fundamental "Advances in Black Personality Theory." Mental health is then shown to be rooted in the original human's biogenetic nature, and, hence, the natural order. Both ordered and disordered personality functioning are considered in this context. The nosology systematizes 18 of the disorders of the African per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(68 citation statements)
references
References 12 publications
1
66
1
Order By: Relevance
“…This supports 7 the postulation that compared to White communities; members of Black communities are more 8 likely to perceive mental disorders as a weakness in character. Similarly, it strengthens 9 existing claims that some African American populations might consider mental disorders as 10 indicative of disharmony or dysfunction within the community (Azibo, 1989;Myers, 2003); 11 leading to silence around depression or symptoms that might be thought to be at odds with 12 perceptions of harmony, strength and resilience.…”
supporting
confidence: 57%
“…This supports 7 the postulation that compared to White communities; members of Black communities are more 8 likely to perceive mental disorders as a weakness in character. Similarly, it strengthens 9 existing claims that some African American populations might consider mental disorders as 10 indicative of disharmony or dysfunction within the community (Azibo, 1989;Myers, 2003); 11 leading to silence around depression or symptoms that might be thought to be at odds with 12 perceptions of harmony, strength and resilience.…”
supporting
confidence: 57%
“…Stated Kerr (2005), ''It is no surprise that in every nation that had contact with the African slave trade, there is a version of color politics playing out in terms of economic, political, and social power'' (p. 273). Lacking a strong, collective African identity (Azibo, 1989), Black people in the United States are particularly susceptible to mainstream or dominant cultural messages that devalue physical features common to African people. Not surprisingly, Black social organizations and institutions have participated in discriminating against darker skinned Blacks (Gatewood, 1990;Russell, Wilson, & Hall, 1992).…”
Section: Hair As Race: Creating a Color Complexmentioning
confidence: 99%
“…African American elders are most likely to experience poverty, with poverty rates more than twice that of all other older Americans (Beedon & Wu, 2004). There is now a sizable literature documenting the systematic discrimination experienced by African Americans (Azibo, 1989;Collins, 2000, Neville, Coleman, Falconer, & Holmes, 2005; analyses have suggested that exposure to such discrimination, including media portrayals of negative aging stereotypes, is associated with negative health conditions (Levy, 2005, as cited in Currey, 2008). These conditions may be exacerbated in the lives of older Black LGBT persons, however, in their either misrepresentation or, more commonly, under-representation in media and related images of all sorts.…”
Section: Literature Reviewmentioning
confidence: 99%